Identification of rare de novo epigenetic variations in congenital disorders - Mafalda Barbosa (Nature Portfolio, 2018)
A proportion of neurodevelopmental disorder and congenital anomaly cases remain without a genetic diagnosis. Here, the authors study aberrations of DNA methylation in such cases and find that epivariations might provide an explanation for some of these undiagnosed patients.